Rare earth element content in the SPM of Daliao river system and its comparison with that in the sediments, loess and soils in China - 林春野 何孟常 李艳霞 杨林生 刘瑞民 杨志峰 (Journal of rare earths, 2008)
Content and distribution patterns of rare earth dements （REEs） in the suspended particulate material （SPM） of Daliao River system were investigated and compared with those in the fiver and sea sediments, loess, and soils of China. Twenty-seven samples of SPM were taken in Daliao River system and digested with various acids followed by ICP-MS analysis for REEs and ICP-OES analysis for Al, Fe, Mn, Ti, Mg, Ca, Na, and K, to measure the total concentrations of these elements. Results indicated that the spatial change in the content of REEs was great, with the coefficient of variance （CV） from 84% to 105%, while the contents of REEs were significantly correlated with each other. Chondrite-normalized patterns of REEs were characterized by higher enrichment of light REEs than heavy REEs, and a depletion of Eu in the SPM was generally found. The positive anomaly of Eu in the SPM of Xi River was due to anthropogenic source in Shenyang City. Furthermore, chondfite- and upper continent crust-normalized patterns of REEs in the SPM of Daliao River system, sediments of Yangtze River and Yellow River, sediments of Yellow Sea, East Sea, South Sea of China, and loess and soil of China, were very similar to one another. These demonstrated that the weathering and sedimentary processes resulted in constant REE distribution not only in the typical sedimentary rocks, but also in the modem riverine particle, sea sediments, loess, and soils.